Electrospun Highly Ordered Mesoporous Silica–Carbon Composite Nanofibers for Rapid Extraction and Prefractionation of Endogenous Peptides. Issue 11 (30th January 2015) - Zhu, Gang‐Tian; Chen, Xi; He, Xiao‐Mei; Wang, Han; Zhang, Zheng; Feng, Yu‐Qi
Abstract A simple method was developed for the preparation of ordered mesoporous silica–carbon composite nanofibers (OMSCFs). The OMSCFs exhibited high carbon content, continuously long fibrous properties, uniform accessible mesopores, and a large surface area. The OMSCFs were also found to have ion‐exchange capacity. On the basis of the size‐exclusion effect of the mesopores and mixed‐mode hydrophobic/ion‐exchange interactions, the OMSCFs were applied for rapid enrichment of endogenous peptides by using a miniaturized solid‐phase extraction format. The adsorption mechanism was studied, and the eluting solution was optimized with standard peptide/protein solutions and protein digests. Employing a successive three‐step elution strategy, followed by LC‐MS/MS analysis, led to excellent performance with this approach in the extraction and prefractionation of peptides from human serum.